National Insurance Against Sickness and Unemployment : Full explanation of Mr Lloyd George's great scheme - Wilson, Philip Whitwell, 1875- (London : The Daily News)
1911 1911 1910s 4 pages The Daily News PAMPHLET. NATIONAL INSURANCE AGAINST SICKNESS AND UNEMPLOYMENT. Full Explanation of Mr. Lloyd George's Great Scheme. (By P.W. WILSON.) I am asked to state in simple language what is meant by the great National Insurance Bill, as introduced into the House of Commons by Mr. Lloyd George. The Bill contains about eighty clauses, and is thus a very bulky measure. It is divided into two parts. The first part provides insurance against sickness and disablement ; the second part provides insurance against unemployment. I will begin with Part 1. The sickness insurance is compulsory on all who earn weekly wages or earn salaries under the income-tax level of £3 a week. The chief exceptions are: 1. The Army and Navy, for which special provision is to be made ; 2. Teachers, whose case, both in Great Britain and Ireland, is to be separately handled ; 3. Crown servants and municipal employees, provided that they already have their own schemes ; 4. Commission agents, tradesmen, and other persons, like the village blacksmith, who earn an income under £3 a week, but are not regularly employed by any one person. For these latter, as we shall see, a voluntary branch is to be provided. Casual labour is as far as possible to be included. Indeed, Mr. Lloyd George hopes to bring in golf caddies. The compulsory scheme thus covers railwayman, clerks, typists, domestic servants, waitresses, miners, and, indeed, the whole range of ordinary industry. The word compulsion may seem, perhaps, a little harsh, but when the benefits of the scheme are appreciated, very little pressure will be required to bring people in. Contributions will be generally of 4d. a week for men, 3d. from the employer, and 2d. from the State. Total, 9d. a week. Women workers will pay 3d. a week instead of 4d., and the total in their case would be 8d. a week. Special provision is made for low wages. Thus, where a man or woman earns less than 15s. a week he or she will pay a reduced contribution, and the employer who pays the low wages must make up the balance. The scale for low wages is, thus: Daily Pay. Employer's Contribution. Worker's Contribution. Men. Women. 2s. 6d. or under 4d. 3d. 3d. 2s. or under 5d. 4d. 2d. 1s. 6d. or under 6d. 5d. 1d. To these contributions, amounting to 7d. for men and 6d. for women, the State will, as usual, add 2d., so that even where wages are low the Insurance Fund will receive 9d. a week on behalf of every man, and 8d. a week on behalf of every woman. This special provision for wages below 15s. a week will particularly affect factory girls in London and other centres, and agricultural labourers in certain English counties. It will not concern domestic servants, who do certainly receive in cash less than 15s. a week, but who in addition have board and lodging. In reckoning the wage, board and lodging, if furnished by the employer, must be added. The age limits are from the date of first employment — 14, 15, 16 years, that is, right up to 65 years of age, after which age no one will be admitted. Married women not in employment outside their own domestic duties will be excluded from paying into the scheme, and from all direct benefits, save the maternity allowance mentioned below. But there are about 700,000 married women earning wages from employers, and these married women will come under the compulsory provisions. They will pay their weekly contributions just as if they were single, and will be eligible for all benefits. THE VOLUNTARY MEMBERSHIP. For persons like the village blacksmith, the small tradesman, the outside porter, the boot-black, the window-cleaner, the chimney-sweep, etc., who are their own employers, a voluntary branch is arranged. These persons may either join the scheme or remain outside, as they like. If they join within a year, they will pay 7d. a week if men, and 6d. a week if women, the State adding 2d. This means that they will pay a sum the equal of what under the compulsory branch of the scheme is to be paid by employer and workman combined. Everyone, therefore, under 65 years old, who earns his own living, has thus an opportunity of sharing the national benefits. Moreover, the voluntary scheme enables Mr. Lloyd George to provide for a difficult case. It enables him to deal with the case of a boy who begins life by earning less than £3 a week, say as a bank clerk. After paying for years into the fund, he obtains promotion, which brings his income above the compulsory limit. Is he then excluded from 345/3/2/2